PROBLEMS AND PROSPECTS OF TOURISM EDUCATION DEVELOPMENT IN UKRAINE - Зубехіна, Тетяна Василівна; Terletsky, Volodymyr; Olhova-Marchuk, Natalia; Kushnir, Volodymyr (Educological discourse, 2021)
The article analyzes the problems and prospects of tourism education in Ukraine. It is established that the level of socio-cultural development of any country directly depends on the level of development of the tourism industry and the relevant qualifications of human resources. It was found that today there is a need to train professionals in the field of tourism, who have competencies in the use of new technologies and software, marketing tools to promote tourism products and services, communication and psychological skills, orientation in modern trends in tourism and etc. The normative-legal base of tourism education systems in Ukraine is considered. It is determined that our country is still on the way to implementing key existing laws and regulations aimed at the Europeanization of education, including tourism education. The impact of the COVID-19 pandemic on the education system, in particular in the field of tourism, has been studied. It is concluded that the availability of an education and training system suitable for the digital age is very important in modern conditions. It is established that future specialists in the field of tourism do not have sufficient practical experience after graduating from higher education institutions. It is concluded that their practical training plays an important role in the training of future highly qualified employees. The necessity of using foreign experience in training specialists in the field of tourism, which will help domestic tourism education to enter the international standardized system, is substantiated. Perspective directions of modernization of the domestic system of tourist education in the context of European integration processes are outlined, namely: strengthening of the practical component of tourist education, providing access to foreign internships; adjustment of educational programs taking into account world trends and needs of tourists; stimulating students and teachers to international exchange of experience and internships, etc.